Designing a PjBL-Based Textbook on Lamp Civilization for Children's Self-Regulation Character Development - Gregorius Ari Nugrahanta; Hilary Relita Vertikasari Sekarningrum; Eusebius Aditya (Lembaran Ilmu Kependidikan, 2025)
Background - Limited self-regulation skills among elementary students pose a significant educational challenge, necessitating structured interventions. Current efforts are often sporadic and minimally integrated into learning. Self-regulation involves managing cognition, emotions, and behavior to achieve goals. Purpose - This study develops a Project-Based Learning (PjBL)-based textbook on lamp civilization to enhance self-regulation Method - Using the ADDIE model within a Research and Development (R&D) framework, the study followed five stages: analysis, design, development, implementation, and evaluation. Implementation involved 23 elementary students selected via convenient sampling. Findings - Findings indicate that: 1) The textbook was successfully developed within the ADDIE model, ensuring structured learning. 2) Expert evaluations rated the textbook as excellent (3.84/4), confirming high quality. 3) Implementation significantly improved self-regulation (p < 0.05), with a large effect size (r = 0.9796, 95.96%) and a high N-Gain Score (96.19%). Conclusion - These results underscore the effectiveness of structured pedagogical materials in fostering self-regulation. The genetic approach within a PjBL framework provides an innovative model for integrating historical and technological literacy. Future research should examine its long-term impact, broader applicability, and employ randomized trials for enhanced generalizability. Novelty/Originality/Value - Novelty employing a genetic approach as its novelty that traces lamp development from its origins to modern advancements. This method fosters inquiry, problem-solving, historical reasoning, technological literacy, and character development.